The Unethical Practices of the Pharmaceutical Industries in Bangladesh in their Drug Promotion and its Impacts - Md. Abdul Awal; Md. Shishir Saidy; Md. Aliullah (International Journal of Engineering and Management Research, 2021)
This article highlights the unethical practices of pharmaceutical industries in Bangladesh in their drug promotion and its impacts. It is evident that pharmaceutical industry is one of the promising sectors in the industrial field of Bangladesh. Now, the pharmaceutical industries of Bangladesh are exporting their products to more than 100 countries in the world after meeting the local demand. This study also represents the growth and market share of pharmaceutical industries, total exports of last five years, unethical practices in promotion of pharmaceutical industries and impacts of unethical practices. To conduct the study both secondary and primary data have been used. The target population of this study was medical professional men including physicians of Phultala Thana in Khulna District. Finally the study provides some recommendations to overcome the situation. There are a lot of rooms for Bangladesh to develop in this sector. In this study, the unethical practices in promotion of pharmaceutical industries that can make obstacle in the sustainable growth of pharmaceutical business in Bangladesh are discussed meticulously.